1985
DOI: 10.1159/000233823
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Antibodies to Guinea Pig IgE and Its Use for Enzyme-Linked Immunosorbent Assay of IgE Antibodies

Abstract: Guinea pigs were infected with Trichinella spiralis. A pooled serum from the infected guinea pigs was fractionated by DEAE-cellulose column chromatography and Sephadex G-200 gel filtration. An IgE-rich fraction was injected into rabbits. The antiserum from the rabbits, after appropriate absorption with a normal guinea pig plasma, formed a precipitin line in immunoelectrophoresis and in immunodiffusion against a guinea pig serum containing IgE antibodies to ovalbumin. Uptake of 125I ovalbumin was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Antigen binding activity of both antibodies in the serum will give us such information. Recently we could obtain rabbit anti-guinea pig IgE [12]. This antiserum may enable these studies to be carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antigen binding activity of both antibodies in the serum will give us such information. Recently we could obtain rabbit anti-guinea pig IgE [12]. This antiserum may enable these studies to be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…The other 5 sensitized guinea pigs showed a similar reaction at the inhalation of OA. was observed when examined by radioimmuoelectrophoresis [12].…”
Section: Characteristic O F Gp-oa Ige Preparedmentioning
confidence: 99%
“…The ELISA was also validated using serum samples from normal and OVA-sensitized guinea pigs for measurement of the IgE mass concentrations. In a 1985 report based on preliminary experiments, Ito et al showed that a rabbit anti-guinea-pig IgE polyclonal antibody could be raised using IgE-rich fraction purified from the pooled serum of guinea pigs infected with Trichinella spiralis as an immunogen and also demonstrated the possibility of establishing an ELISA for guinea pig IgE (22). They also reported development of an ELISA using OVA/ mite extract-coated wells to measure the levels of IgE antibodies to OVA / mite for comparison with titers determined by PCA (11).…”
Section: Discussionmentioning
confidence: 99%
“…Guinea-pig IgE was purified from pooled sera of guinea pigs (female Hartley, about 600 g of body weight; SLC Japan, Inc., Hamamatsu) that had been sensitized eight times at two-week intervals with 10 µg of ovalbumin (OVA; ICN Biochemicals, Aurora, OH, USA) in 4 mL of aluminum hydroxide gel prepared in our laboratory and 2.5 × 10 10 cells of Pertussis Vaccine (Wako Pure Chemical Industries Ltd., Osaka) per animal based on Ito's method with some modifications (11,22). The method for purification consisted of salting-out with saturated ammonium sulfate and ion-exchange chromatography.…”
Section: Standard Guinea Pig-igementioning
confidence: 99%
See 1 more Smart Citation